Kewenangan Pemerintah Daerah dalam Pengelolaan ZIS: Analisis Peraturan Daerah Pasca Undang-Undang Nomor 23 Tahun 2011: Local Government Authority in the Management of ZIS: An Analysis of Local Regulations Following Law No. 23 of 2011 - Landi Iskandar (SIYASI: Jurnal Trias Politica, 2024)
This study examines the development of Zakat, Infaq, and Sedekah (ZIS) management from a legislative perspective in Indonesia. The research problem focuses on the authority of local governments to establish regional regulations regarding ZIS management after the enactment of Law Number 23 of 2011 on Zakat Management. This research employs a normative juridical method with a statute approach to analyze the authority of regional regulation formation and its relationship with the hierarchy of legislation. The findings reveal that local governments do not have the authority to establish regional regulations on ZIS management because zakat management is a religious affair under the authority of the central government. The national authority for ZIS management rests with the National Zakat Agency (BAZNAS), established under Law Number 23 of 2011, without any delegation of authority to local governments to regulate through regional regulations. This study concludes that the establishment of regional regulations on ZIS by local governments is inconsistent with the principles of attribution and delegation of authority in the formation of legislation.